Analysis of students’ thinking process in solving arithmetic sequence based on adversity quotient types - Muhamad Sabirin; Saidah Arafah; M. Amin Paris; Muh. Fajaruddin Atsnan; Maisea Ledua Nareki (Department of Mathematics Education, Faculty of Mathematics and Natural Sciences, UNY, 2021)
This descriptive qualitative study aimed at describing students’ thinking process in solving arithmetic sequence problems based on students’ adversity quotient (AQ). Two students who have camper type of AQ and two students who have transition from camper to climber type of AQ were involved in this study. We employed a questionnaire to identify the type of AQ that students have, a test to collect data on students’ problem-solving process, and an interview guideline to clarify students’ thinking process in problem-solving. The collected data were analyzed by following a process consisting of data reduction, data presentation, and drawing conclusions or verification. The results revealed that the students who have camper type of AQ demonstrated an assimilation thinking process on the stage of understanding problem and devising a problem-solving plan, an accommodation-assimilation thinking process on the stage of devising a problem-solving plan, and an accommodation thinking process on the stage of looking back. As for students who have transition from camper to climber type of AQ, they have similar thinking process with that of the students who have camper type of AQ on the stage of understanding problem, devising a problem-solving plan, and executing the problem-solving plan, but these students demonstrated different thinking process on the stage of looking back. In the stage of looking back, the students who have transition from camper to climber type of AQ presented an accommodation-assimilation thinking process that can be found from their responses to the test and interview.